2019
DOI: 10.1002/jcph.1402
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Dose Pharmacokinetics and Safety of Solriamfetol in Participants With Normal or Impaired Renal Function and With End‐Stage Renal Disease Requiring Hemodialysis

Abstract: Solriamfetol (JZP‐110), a selective dopamine and norepinephrine reuptake inhibitor with wake‐promoting effects, is renally excreted ∼90% unchanged within 48 hours. Effects of renal impairment and hemodialysis on the pharmacokinetics and safety of 75‐mg single‐dose solriamfetol were evaluated in adults with normal renal function (n = 6); mild (n = 6), moderate (n = 6), or severe (n = 6) renal impairment; and end‐stage renal disease (ESRD) with and without hemodialysis (n = 7). Relative to normal renal function,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Solriamfetol C max and t max values are not substantially affected by mild to severe renal impairment [29]. However, there are incremental decreases in clearance with worsening renal function, and these correspond to increases in AUC ∞ (53%, 129%, 339%) and t ½ (1.2-, 1.9-, 3.9-fold) in mild, moderate and severe renal impairment, respectively, relative to no renal impairment.…”
Section: Pk/ddi Potentialmentioning
confidence: 88%
“…Solriamfetol C max and t max values are not substantially affected by mild to severe renal impairment [29]. However, there are incremental decreases in clearance with worsening renal function, and these correspond to increases in AUC ∞ (53%, 129%, 339%) and t ½ (1.2-, 1.9-, 3.9-fold) in mild, moderate and severe renal impairment, respectively, relative to no renal impairment.…”
Section: Pk/ddi Potentialmentioning
confidence: 88%
“…3 The PK profile of solriamfetol in this study is consistent with what has previously been reported in healthy adults. 5,6 Solriamfetol was rapidly absorbed, with a median t max of 2 and 3 hours following oral administration of 300-and 900-mg doses, respectively. An approximately 3-fold higher solriamfetol C max and 3.5-fold greater AUC 0-inf were observed following the 900-mg dose compared with the 300-mg dose, indicating dose-proportional PK.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 As previously noted, the 300-mg dose was the highest dose evaluated in phase 3 studies in participants with narcolepsy or OSA. [7][8][9] The 900-mg dose was selected for this study because it was likely to be the highest dose that could be studied without having an adverse impact on tolerability or study discontinuation and because it was predicted to result in exposures greater than what would be estimated in individuals who might have increased exposure to therapeutic doses of solriamfetol (eg, those with renal impairment 6 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although elimination can occur through several routes, most small‐molecule drugs are cleared by elimination of unchanged parent drug via the kidney and/or by metabolism in the liver and/or gastrointestinal tract. If the elimination of a drug is predominantly through the renal excretory pathway, impaired renal function usually alters the drug's exposure to the extent that the dosage regimen needs to be changed for patients with various degrees of renal impairment from that used in patients with normal renal function, especially for drugs with a narrow therapeutic index . Therefore, assessing the effect of organ impairment (including renal impairment and hepatic impairment) on drug exposure is required for all investigational drugs.…”
Section: Discussionmentioning
confidence: 99%